Confirmation of CAGSSS syndrome as a distinct entity in a Danish patient with a novel homozygous mutation in IARS2. Issue 4 (22nd March 2017) - Moosa, Shahida; Haagerup, Annette; Gregersen, Pernille Axel; Petersen, Karin Kastberg; Altmüller, Janine; Thiele, Holger; Nürnberg, Peter; Cho, Tae‐Joon; Kim, Ok‐Hwa; Nishimura, Gen; Wollnik, Bernd; Vogel, Ida
Abstract : Since the original description of the IARS2 ‐related cataracts, growth hormone deficiency, sensory neuropathy, sensorineural hearing loss, skeletal dysplasia syndrome (CAGSSS; OMIM 616007) in an extended consanguineous family of French–Canadian descent, no further patients have been reported. IARS2 (OMIM 612801) encodes the mitochondrial isoleucine‐tRNA synthetase which belongs to the class‐I aminoacyl‐tRNA synthetase family, and has been implicated in CAGSSS and a form of Leigh syndrome. Here, we report on a female Danish patient with a novel homozygous IARS2 mutation, p.Gly874Arg, who presented at birth with bilateral hip dislocation and short stature. At 3 months, additional dysmorphic features were noted and at 18 months her radiographic skeletal abnormalities were suggestive of an underlying spondyloepimetaphyseal dysplasia (SEMD). Retrospective analysis of the neonatal radiographs confirmed that the skeletal changes were present at birth. It was only with time that several of the other manifestations of the CAGSSS emerged, namely, cataracts, peripheral neuropathy, and hearing loss. Growth hormone deficiency has not (yet) manifested. We present her clinical features and particularly highlight her skeletal findings, which confirm the presence of a primary SEMD skeletal dysplasia in a growing list of mitochondrial‐related disorders including CAGSSS, CODAS, EVEN‐PLUS, and X‐linked SEMD‐MR syndromes.